The effect of permeability enhancement on dry-out behavior of CA- and microsilica gel-bonded castables as determined by NMR. Issue 9 (15th June 2020) - Barakat, A.J.; Pel, L.; Adan, O.C.G.; Myhre, B.; Peng, H.; Wöhrmeyer, C.; Krause, O.
Abstract: This investigation deals with refractory monolithic materials that are broadly used in thermal treatment facilities as they are necessary e.g. for iron and steel, glass and cement production, thereby withstanding temperatures between 600 and 2000 °C. In the special case of hydraulic bond refractory castables, the components must be mixed with water for two reasons: firstly, to obtain a mouldable suspension; and secondly, to achieve a green strength via the hydraulic reaction of calcium aluminate cement that is high enough to enable a secure refractoriness of the concrete formwork. Prior to their first use in production, castables must have their pore water and hydraulic bond water carefully removed in order to avoid explosive spalling that can cause severe damages inside the furnaces. In this study, we investigate the one-dimensional drying behavior of two specific refractory castable compositions, a microsilica-containing low- and a no-cement castable (LCC/NCC) during first heat-up in the temperature regime between 20 and 300 °C. First results were already presented in a prior publication that demonstrate a specialized high-temperature Nuclear Magnetic Resonance (NMR) setup capable of continuously measuring moisture and temperature profiles on 74 mm-long cylindrical samples, without touching or moving the sample [1]. In this paper we explore how the use of permeability-enhancing agents (fibers and MIPORE 20) beneficially affects the drying behavior and consequently allows higher heating rates. We also demonstrate that the NMR technique as applied here is sensitive enough to resolve differences in the dry-out behavior if said additives are used in the castable formulations. Our results demonstrate that incorporation of fiber and MIPORE 20 significantly alters the dry-out behavior. In particular, it can be resolved that as the fibers begin to melt, there is a noticeable increase in permeability that results in faster drying, as well as a decrease of the drying front temperature and therefore the generated maximum pressure.